2017
DOI: 10.1002/joc.5103
|View full text |Cite
|
Sign up to set email alerts
|

The climatology of the Red Sea – part 1: the wind

Abstract: The wind climatology of the Red Sea is described based on a 30‐year high‐resolution regional reanalysis generated using the Advanced Weather Research Forecasting model. The model was reinitialized on a daily basis with ERA‐Interim global data and regional observations were assimilated using a cyclic three‐dimensional variational approach. The reanalysis products were validated against buoy and scatterometers data. We describe the wind climatology and identify four major systems that determine the wind patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…Furthermore, all data sets suggest that the warming trend exhibits a North-South gradient, with higher warming rates in the Northern Red Sea (Figure 1-lower panel). Langodan et al (2017) reported a gradual reduction of wind strength during the last decades over the Northern Red Sea, which is consistent with the warming SST trend. These spatial patterns are better captured by the two highresolution data sets (AVHRR-OI, OSTIA), but are also pronounced in the lower resolution (HadSST, ERSSTv5) products.…”
Section: Recent Sst Trends (Satellite Era) In the Red Seasupporting
confidence: 83%
“…Furthermore, all data sets suggest that the warming trend exhibits a North-South gradient, with higher warming rates in the Northern Red Sea (Figure 1-lower panel). Langodan et al (2017) reported a gradual reduction of wind strength during the last decades over the Northern Red Sea, which is consistent with the warming SST trend. These spatial patterns are better captured by the two highresolution data sets (AVHRR-OI, OSTIA), but are also pronounced in the lower resolution (HadSST, ERSSTv5) products.…”
Section: Recent Sst Trends (Satellite Era) In the Red Seasupporting
confidence: 83%
“…Regulated by the mountains on both the east and west coasts, the winds over the central Red Sea blow orographically along the axis of the basin. The wind speed is affected by large‐scale atmospheric conditions over the Mediterranean Sea and the northern Indian Ocean (Langodan et al, ). In addition, during winter, the northwest winds meet the southeast winds in the central Red Sea to form the Red Sea convergence zone (Viswanadhapalli et al, ).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A 38‐year (1980–2018) high‐resolution reanalysis (Viswanadhapalli et al ., ; Langodan et al ., , ; Bindu et al ., ; Dasari et al ., ; Viswandhapalli et al ., 2019), generated using the Weather and Research Forecasting (WRF) model (Skamarock et al ., ) and ERA‐Interim (ERA‐I) reanalysis (Dee et al ., ), was used to study the prevailing anomalous atmospheric circulation patterns over Kerala in August 2018. Generally, global reanalyses provide acts as a good source of information for studying severe weather conditions.…”
Section: Methodsmentioning
confidence: 99%